Cultural continuity and symbolic shifts: artistic patterns in beverage containers during the Xia, Shang and Zhou periods - Weifan Wang (Trans/Form/Ação)
This article explores the evolution of symbolic patterns in wine vessel art patterns during the Xia, Shang and Zhou dynasties, from the perspective of historical development, through literature review and pattern comparison. By analyzing the characteristics and cultural origins of symbolic patterns, inspiration has been provided for modern design. The results indicate that, influenced by aesthetic concepts and dominant ideas, the artistic patterns of wine vessels mainly include animal patterns, geometric patterns and natural patterns. The patterns from different dynasties reflect the changes in social systems, religious beliefs and aesthetic concepts, reflecting the spirit of our ancestors’ pursuit of beauty and reverence for order in daily life. The conclusion indicates that the artistic patterns of wine vessels, during the Xia, Shang and Zhou dynasties, were not only decorative, but also carriers of culture and philosophy. Analyzing the symbolic meanings, behind patterns, cultural concepts and social changes, can enrich our understanding of the development of ancient art and promote the development of traditional culture.